Contribui??es no Desenvolvimento do Servi?o Novagenesis Embarcado para Internet das Coisas - Magalh?es, V?ner Jos? (2017)
The Internet of things is becoming one of the key applications for future Internet architectures. Since many believe that the majority of Internet devices will become sensors and actuators equipped over ordinary \things", like cars, lampposts, parking lots, city squares, etc., it makes a lot of sense to think on the Internet of things as one of the most important requirements for the future Internet (FI). In this dissertation, an extension of the NovaGenesis (NG) future Internet is presented in order to adapt it to the IoT world. The NG is presented in its original form and then a new service is proposed to run embedded in devices with restricted capabilities. This new service has been called \Embedded Proxy/Gateway Service" (EPGS). With the use of NG via EPGS, a Future Internet of Things (FIoT) is created, introducing ingredients such as: information-centric networking for IoT data exchanging, storage, and processing;service-oriented architecture of IoT dynamic IoT services composition; and software-control for IoT devices management and operation. NovaGenesis unlimited naming and name resolution is applied to forward and route IoT raw data with provenance and integrity. IoT services are dynamically composed, creating a data chain from device representative/gateway services to interested applications. Some experimental scenarios were evaluated in order to demonstrate the NovaGenesis architecture for IoT using the proposed new service. Finally, some limitations are listed and some suggestions for improvements and future work are presented.